2008
DOI: 10.1161/hypertensionaha.108.111674
|View full text |Cite
|
Sign up to set email alerts
|

Valsartan Improves Arterial Stiffness in Type 2 Diabetes Independently of Blood Pressure Lowering

Abstract: Abstract-Increased arterial stiffness, as estimated from aortic pulse wave velocity (Ao-PWV), and albuminuria are independent predictors for cardiovascular disease in type 2 diabetes mellitus (T2DM). Whether angiotensin receptor blockers (ARBs), drugs with cardio-renal protective effects, improve Ao-PWV to a greater extent than other equipotent antihypertensive medications remains unclear. After a 4-week washout phase, we compared the effects of valsartan (nϭ66), an ARB, with that of amlodipine (nϭ65), a calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 55 publications
4
76
0
19
Order By: Relevance
“…Strong renoprotection by ARBs, but not other antihypertensive drugs, via a reduction in proteinuria is well known, in addition to direct BPlowering effects 31,32) . In addition, several reports have shown that ARBs improve the arterial stiffness, as assessed by the pulse wave velocity 33,34) . Especially in CKD patients, superior preventive effects for olmesartan on nocturnal hypertension and proteinuria have been suggested compared to other ARBs 35,36) .…”
Section: Inhibitory Effects Of the Arbmentioning
confidence: 99%
“…Strong renoprotection by ARBs, but not other antihypertensive drugs, via a reduction in proteinuria is well known, in addition to direct BPlowering effects 31,32) . In addition, several reports have shown that ARBs improve the arterial stiffness, as assessed by the pulse wave velocity 33,34) . Especially in CKD patients, superior preventive effects for olmesartan on nocturnal hypertension and proteinuria have been suggested compared to other ARBs 35,36) .…”
Section: Inhibitory Effects Of the Arbmentioning
confidence: 99%
“…However, what determines progression or regression of aortic stiffness over the long-term, which is critical to planning long-lasting interventions to reducing arterial stiffness, remains unsettled. Indeed, most prospective studies evaluated the effects of pharmacological or nonpharmacological interventions in the short-term of few months up to a year (11,12) or only measured cf-PWV once at the end of follow-up (13,14). Few prospective studies evaluated serial changes in cf-PWV and their correlates over the long-term of at least 2-3 years (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Однако из-за нехватки качественных РКИ с достаточной статистической мощностью остается неясным, превосходят ли эти препараты по своему влиянию на жесткость артерий другие антигипертензивные средства. Способность блокаторов РАС уменьшать жесткость артерий, о кото-рой судят по СПВ, по-видимому, не зависит от их спо-собности снижать АД [582][583][584]. Однако несмотря на то, что комбинация амлодипина с валсартаном снижала центральное САД более эффективно, чем комбинация амлодипина с атенололом, в исследова-нии EXPLOR обе комбинации уменьшали СПВ на 0,95 м/сек, без значимых различий на протяжении 24 недель [399].…”
Section: повышенная жесткость артерийunclassified